War as Conflict Resolution in Syair Perang Menteng (Melayu: Jurnal Antarabangsa Dunia Melayu, 2022)
This study discusses war as conflict resolution in Syair Perang Menteng. The objective of this study is to clarify the conflict between Sultan Mahmud Badaruddin II and Muntighe that was resolved by war only. It is undeniable that several methods were used to avoid a war from happening, but all of them failed to reach an agreement. To discuss in detail, the war theory that Sun Tzu introduced in his book, The Art of War (2002), was used to achieve the objective of this study. Sun Tzu has listed 13 war strategies, which are valuation, battle launching, planning attack, strategic positions, strategic advantages, weaknesses and strengths of armed conflict, adapting to the nine possibilities, deploying troops, terrain, nine types of terrain, arson attacks, and using spies. Based on the analysis of Syair Perang Menteng, Sultan Mahmud Badaruddin II applied this strategy in the war against the Dutch. In addition to the strategies based on Sun Tzu’s views, Sultan Mahmud Badaruddin II also had superiority in forming war strategies. Among the superior strategies owned by Sultan Mahmud Badaruddin II was placing Allah and the Islamic faith as the primary basis of the war against the Dutch and having the full support and obedience of the Palembang community. The superiority of this war strategy successfully gave victory to the Palembang side in this battle, and they successfully resolved the conflict between these two sides through war.Full text: PDF